Advancing the science of unfinished nursing care: Exploring the benefits of cross‐disciplinary knowledge exchange, knowledge integration and transdisciplinarity - Jones, Terry; Willis, Eileen; Amorim-Lopes, Mário; Drach-Zahavy, Anat; Papastavrou, Evridiki; Lemonidou, Chryssoula; Sermeus, Walter; Suhonen, Riitta; Riklikiene, Olga; Acaroglu, Rengin; Andreou, Panayiota; Antonic, Darijana; et al. (My University, 2019)
Aims The aims of this paper are to explore the role of cross-disciplinary knowledge exchange and integration in advancing the science of unfinished nursing care and to offer preliminary guidance for theory development activities for this growing international community of scholars. Background Unfinished nursing care, also known as missed care or rationed care is a highly prevalent problem with negative consequences for patients, nurses and healthcare organizations around the world. It presents as a 'wicked' sustainability problem resulting from structural obstacles to effective resource allocation that have been resistant to conventional solutions. Research activity related to this problem is on the rise internationally but is hindered by inconsistencies in conceptualizations of the problem and lack of robust theory development around the phenomenon. A unified conceptual framework is needed to focus scholarly activities and facilitate advancement of a robust science of unfinished nursing care. Design Discussion paper. Data Sources This discussion paper is based on our own experiences in international and interdisciplinary research partnerships related to unfinished nursing care. These experiences are placed in the context of both classic and current literature related to the evolution of scientific knowledge. Implications for Nursing The problem of unfinished nursing care crosses multiple scientific disciplines. It is imperative that the community of scholars interested in solving this wicked problem engage in meaningful cross-disciplinary knowledge integration and move towards transdisciplinarity. Conclusion Metatheorizing guided by structuration theory should be considered as a strategy to promote transdiciplinarity around the problem of unfinished nursing care.
Keywords: Interdiciplinarity; Knowledge integration; Missed care; Multidisciplinarity; Rationed care; Social sustainability; Structuration theory; Theory development; Transdisciplinarity; Unfinished nursing care